Skip to main content

Iteration method or successive approximation method.

 Iteration method

To find the real root of an equation f (x)=0 ...(1)
Which can be expressed in the form x=πœ™(x) ......(2)
First we find an initial approximate value x₀ for equation (1). The better approximation x₁ for the root is obtained by replacing x by x₀  in R.H.S of equation (2) i.e x₁ = πœ™(x₀)
A still better approximation x₂ for the root is obtained by putting x=x₁ in the R.H.S of equation (2). Thus x₂ = πœ™(x₁).
This procedure is continued and we get
x₃ =  πœ™(x₂)
x₄ =  πœ™(x₃)
.................
xβ‚™ =  πœ™(xβ‚™₋₁)
If the sequence x₀,x₁,x₂,.......xβ‚™ of approximate roots converges to a limit 𝛂, then 𝛂 is taken as the root of the equation f(x)=0.
Remarks
The sufficient condition for convergence of iterations:
1) If I is the interval in which the root  𝛂 of the equation x=πœ™(x) lies, then |πœ™'(x)|< 1 for all x in the interval I.
2) The initial approximation x₀ for the root lies in I.
Example: Find the real root of the equation x³+x²-100=0, by iteration method.
Solution. Given f(x) = x³+x²-100 = 0
f(1) = -98
f(2) = -88
f(3) = -64
f(4) = 64+16-100 = -20 (-ve)
f(5) = 125+25-100 = 50 (+ve)
f(4) and f(5) are of opposite sign.
So the root of equation lie between 4 and 5.
The given equation can be written as,
x²(x+1) = 100
or x = 10/√(x+1)
or x = πœ™(x), where πœ™(x) = 10/√(x+1)
Therefore πœ™'(x) = 10×(-1/2)× 1/(x+1)³⁄ ² = -5/(x+1)³⁄ ²
or  |πœ™'(x)| = |-5/(x+1)³⁄ ²| < 1 in the interval (4,5).
So, the iteration method can be applied.
Taking x₀ = 4.2,  then approximations are
x₁ = πœ™(x₀) = 10/√(4.2+1) = 4.3852

x₂ = πœ™(x₁) = 10/√ (4.3852+1) = 4.3092

x₃ = πœ™(x₂) = 10/√ (4.3092+1) = 4.33995

x₄ = πœ™(x₃) = 10/√ (4.33995+1) = 4.32744

x₅ = πœ™(x₄) = 10/√ (4.32744+1) = 4.33252

x₆= πœ™(x₅) = 10/√ (4.33252+1) = 4.33045

x₇ = πœ™(x₆) = 10/√ (4.33045+1) = 4.33129

x₈= πœ™(x₇) = 10/√ (4.33129+1) = 4.33095

x₉ = πœ™(x₈) = 10/√ (4.33095+1) = 4.33109

x₁₀ = πœ™(x₉) = 10/√ (4.33109+1) = 4.33103

Since x₉ = x₁₀ = 4.3310 correct up to four decimal places.
Therefore, root  is x = 4.3310 Ans.

Comments

Popular posts from this blog

Gauss's central difference formula for equal intervals.

 Gauss's central difference formula for equal intervals: We shall develop central difference formulae which are best suitable for interpolation near the middle of the tabulated set (table). x:             x₋₂  x₋₁  x₀  x₁  x₂ y=f(x):    y₋₂  y₋₁  y₀  y₁  y₂ Difference table. Gauss's forward interpolation formula for equal intervals: f(x) = y₀+[u/1!]∆y₀+{[u(u-1)]/2!}∆²y₋₁+{[(u+1)(u)(u-1)]/3!}∆³y₋₁+{[(u+1)u(u-1)(u-2)]/4!}∆⁴y₋₂ +......., Where u= (x-x₀)/h Remark: This formula is applicable when u lies between 0 and 1 i.e (0<u<1). Example: Using Gauss's forward formula to evaluate y₃₀ given that y₂₁=18.4708, y₂₅=17.8144, y₂₉=17.1070, y₃₃=16.3432 and y₃₇=15.5154. Solution. The difference table is Forward difference table. To find y=f(x) at x=30, i.e f(30): Taking x₀ = 29, h=4, x=30, then u= (x-x₀)/h = (30-29)/4 = 0.25 Using Gauss's forward difference formula f(x) = y₀+[u/1!]∆y₀+{[u(u-1)]/2!}∆²y₋₁+{[(u+1)(u)(u-1)]/3!}∆³y₋₁+[(u+1)u(u-1)(u-2)/4!]∆⁴y₋₂ +...... => f(30)

Different operators

 Different operators We will study the following operators: 1) The Shifting Operator (E): Ef(x) = f(x+h) i.e Ey₀= y₁ E²f(x) = f(x+2h) i.e E²y₀ = y₂ Eⁿf(x) = f(x+nh) i.e Eⁿy₀ = yβ‚™ Here n takes integral or fractional, positive or negative values. For example: E⁻¹f(x) = f(x-h) i.e E⁻¹ y₂ = y₁ E¹/²f(x) = f[x+(1/2)h] i.e E¹/² y₁ = y₃β‚—₂ Properties of Operator E 1) Operator E is distributive. 2) Operator E is commutative with respect to constant. 3) Operator E obeys laws of indices. 2) Forward difference operator (∆): If x₀, x₁,x₂,......., xβ‚™ are equally spaced with interval of differencing h and if y = f(x), then  ∆f(x) = f(x+h) - f(x) i.e ∆yα΅’ = yα΅’₊₁ - yα΅’ for i = 0,1,2,3,..... n-1, The symbol ∆ is called forward difference operator and  ∆yα΅’ is called first forward difference. Similarly, the second forward differences are ∆²yα΅’ =∆yα΅’₊₁ - ∆yα΅’ For example: ∆²y₀ =∆y₁ - ∆y₀ = (y₂ - y₁)-(y₁-y₀)                                   = y₂ -2y₁+y₀ Clearly any higher order differences can easily be expresse

Questions (Forward difference operator, Backward difference operator and Shifting operator)

Questions Example: Given that y₅=4, y₆=3, y₇=4, y₈=10, y₉=24, find the value of ∆⁴y₅: (i) By using the difference table and (ii) Without using the difference table. Solution: (i) Forward difference table. From the difference table ∆⁴y₅=0. Ans. (ii) We have ∆⁴y₅= (E-1)⁴y₅ [∵ ∆=E-1]                               = (E⁴-4E³+6E²-4E+1)y₅                               = E⁴y₅-4E³y₅+6E²y₅-4Ey₅+1y₅                               = y₉ -4y₈+6y₇-4y₆+y₅ [Eⁿyβ‚“=yβ‚“₊β‚™]                               = 24-4×10+6×4-4×3+4                               = 24-40-24-12+4 =0Ans. Example: Given x:  1     2     3      4      5 y:  2     5    10    17    26 Find the value of ∇²y₅. Solution. (i) Backward difference table. From the difference table, we get ∇²y₅=2 Ans. (ii) Without using the difference table to find ∇²y₅: We have ∇²y₅ = (1-E⁻¹)²y₅  [∵ ∇=1-E⁻¹]                          = (1+E⁻² -2E⁻¹)y₅                          = y₅ + y₃ -2y₄ [E⁻ⁿyβ‚“=yβ‚“₋β‚™]                          = 26+10-2×17 = 36-34 = 2 Ans. Example: F